PERANCANGAN MODEL EVALUASI PENDIDIKAN AGAMA ISLAM BERBASIS GOOGLE FORM - Eka Faidah Khasanah; Ma’mun Hanif; Rifqi Lutfiyah; Nafila Mubarokah; Nilna Zulfa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the use of Google Forms as a tool to support online evaluation in Islamic Religious Education (PAI) amid the rapid development of digital technology. The main problem addressed is the limitation of conventional evaluation methods, particularly in terms of efficiency, effectiveness, and data management. This research aims to analyze how Google Forms can facilitate the implementation of learning evaluation. The study employs a qualitative approach using a literature review method, with data collected from relevant scientific journals and analyzed descriptively. The results indicate that Google Forms serves as an effective evaluation medium by simplifying the process of creating, distributing, and analyzing assessment instruments. It allows various forms of evaluation, including multiple-choice, essays, and multimedia-based tasks such as audio, video, and images, enabling assessment across cognitive, affective, and psychomotor domains. Furthermore, the system automatically records and organizes data, making it easier for teachers to evaluate student performance and improve learning strategies. Therefore, the use of Google Forms not only enhances the efficiency of the evaluation process but also improves student engagement and supports the development of a more interactive and adaptive learning environment in the digital era.